"Our child's significant disability shapes our lives": experiences of family social participation. (20th November 2015) - Davey, Heather; Imms, Christine; Fossey, Ellie
Abstract: Purpose : This study explored the stories of parents of youth with severe physical disabilities to understand how they viewed the quality of their family social participation; the barriers to social participation faced as families and the strategies and supports that might be used to reduce these barriers. Method : Ten parents of youth (10–18 years) with severe physical disabilities, recruited through specialist schools, health and disability services, were interviewed using a narratively-oriented interview tool: the Occupational Performance History Interview-II. Interviews were audio-recorded and transcribed verbatim. Narrative and thematic analytic approaches were used to construct each parent's story of family social participation issues, and to identify themes across stories. Results : Parents used highly structured routines and required substantial resources, particularly adult assistance and financial means, to facilitate family social participation. Needs were greater when the youth was more severely impaired, heavier, incontinent or had fragile health. Parents' choice of family activities and belief that they could influence the quality, enjoyment and satisfaction derived from family social participation were shaped by past experiences and the perceived benefits of participation. Conclusions : Family social participation relied on flexible supports tailored to families' needs and preferences. Greater choice and control of resources are central to enabling valued participation. Implications for Rehabilitation: Government resources need to be directed towards improving community based wheelchair accessibility and public toilet facilities for youth with Level V GMFCS-E&R impairments and their families. Disability service delivery models need to enable families to choose the types of high quality care and support that will facilitate valued family social participation. Clinicians need to be aware that families of the most severely impaired children, who are heavier, incontinent or in fragile health, will require substantially more resources than other families to facilitate their social participation.